Methods in Urban Analysis. - (:unkn) unknown (Springer, 2021)
This book highlights major quantitative and qualitative methods and approaches used in the field of urban analysis. The respective chapters cover the background and relevance of various approaches to urban studies and offer guidance in implementing specific methodologies. Each chapter also provides links to real-world examples. The book is unique in its focus on Australian examples and subject matter, presented by recognized experts in the field.
Keywords: Stadtplanung; Stadtforschung; Stadtanalyse; Forschungsmethode; Stadtökonomie; Smart City; Forschungsansatz; Untersuchungsmethode; Datenanalyse; Sekundäranalyse; Interview; Raumbeobachtung; Evaluation; Anwendungsbeispiel; Diskursanalyse